Imagery in sports (1997)
This sixth issue, Imagery in Sports, of Volume 2 of Coaching Science Abstracts reviews articles concerned with imagery and covert behavior activities that can be used in sports. This area is confused, poorly communicated, and rarely exploited in a fully effective manner for athlete gain. Imagery could be used in sports for performance enhancement, skill learning, and covert behavior modification. Coaches normally consider imagery as an activity associated with competition preparation, that is, a performance enhancement function. However, it could be just as and even more effective if used as a feature of skill learning and in the more general domain of behavior modification. To elucidate on these functions this issue breaks from its sole "abstract" tradition and reprints some treatments of all three uses from a number of sources. Topics: - IMAGERY CONCEPTS AND RESEARCH, - APPLIED RESEARCH USING IMAGERY AND OVERT BEHAVIORS, - ATHLETES' STATEMENTS ABOUT IMAGERY, - PROCEDURES FOR COVERT BEHAVIOR APPLICATIONS, - DIFFICULTIES ENCOUNTERED IN IMAGERY RESEARCH - SUGGESTED READINGS.